Elucidating the mechanisms of post-stroke motor recovery mediated by electroacupuncture using diffusion tensor tractography - Kim, Min Su; Moon, Byung Soon; Ahn, Jae-yoon; Shim, Sang-song; Yun, Jong-Min; Joo, Min Cheol (Frontiers in Neurology, 2022)
Acupuncture has been commonly used for post-stroke patients, and electroacupuncture allows simultaneous application of acupuncture and electrical stimulation. We aimed to elucidate the mechanism of electroacupuncture on post-stroke motor recovery using diffusion tensor tractography. A total of 33 subacute stroke patients were recruited. The control group was subjected to conventional rehabilitation therapy, whereas the patients in the experimental group received electroacupuncture therapy for 30 minutes per session for four weeks. Fugl-Meyer assessment of the lower extremity, functional ambulation categories (FAC), and the Korean version of modified Barthel index (K-MBI) were used to compare behavioral outcomes between groups. The corticospinal tract (CST) was examined before and after the intervention via diffusion tensor tractography (DTT) to determine the motor recovery mechanism mediated by electroacupuncture. After four weeks of intervention, both the control and experimental groups showed a significant improvement with respect to FMA_L, FAC, and K-MBI. The level of improvement in FMA_L, FAC, and K-MBI did not vary significantly between the two groups. However, DTT results showed that the CST axial diffusivity of affected side (control: from 0.783 to 0.877, experimental: from 0.840 to 0.897, p=0.003) and its ratio variation (control: from 87.9 to 100.0, experimental: from 95.7 to 100.7, p=0.001) differed significantly between the two groups. The number of fiber tracts and fractional anisotropy of each CST did not show significant intergroup differences. Electroacupuncture played a role in delaying neural degeneration in subacute period after stroke. Thus, electroacupuncture could be an effective adjuvant therapy in addition to conventional rehabilitation for motor recovery after stroke in a long-term perspective.